2012
DOI: 10.1590/s1413-35552012005000052
|View full text |Cite
|
Sign up to set email alerts
|

Breathing exercises in upper abdominal surgery: a systematic review and meta-analysis

Abstract: Background: There is currently no consensus on the indication and benefits of breathing exercises for the prevention of postoperative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
7

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 31 publications
0
42
0
7
Order By: Relevance
“…Common postoperative pulmonary complications include atelectasis, hypoxaemia, pneumonia, respiratory dysfunction and pleural effusion [7,8]. The factors that are directly related to physiological changes include anaesthesia (general or regional), the type of incision, the surgical technique employed.…”
Section: Introductionmentioning
confidence: 99%
“…Common postoperative pulmonary complications include atelectasis, hypoxaemia, pneumonia, respiratory dysfunction and pleural effusion [7,8]. The factors that are directly related to physiological changes include anaesthesia (general or regional), the type of incision, the surgical technique employed.…”
Section: Introductionmentioning
confidence: 99%
“…This study and others (Grams et al 2012, Lunardi et al 2013, Lunardi et al 2015 have demonstrated that DB&C improve respiratory function following UAS, although it remains unclear whether these physiological improvements translate to clinically meaningful reductions in LOS or incidence of PPCs.…”
Section: Postoperative Breathing Exercisesmentioning
confidence: 67%
“…One further systematic review assessed specifically the effect of breathing exercises on physiological aspects of pulmonary function following abdominal surgery such as respiratory muscle strength and diaphragm mobility (Grams et al 2012). This study and others (Grams et al 2012, Lunardi et al 2013, Lunardi et al 2015 have demonstrated that DB&C improve respiratory function following UAS, although it remains unclear whether these physiological improvements translate to clinically meaningful reductions in LOS or incidence of PPCs.…”
Section: Postoperative Breathing Exercisesmentioning
confidence: 94%
“…This can cause a reduction in inspiratory capacity, total inspiratory time, and ventilation at the lung bases, leading to a high risk of developing post operative pulmonary complications (PPCs) [1]. For adequate pulmonary ventilation to occur, it is fundamental that the forces that act on the respiratory system favor the thoracic and abdominal movements, especially the respiratory muscle strength that is compromised after UAS [2].…”
Section: Introductionmentioning
confidence: 99%